2005
DOI: 10.2527/2005.833613x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of novel females and stage of the estrous cycle on sexual behavior in mature beef bulls1,2

Abstract: The objective of this experiment was to determine the effects of unrestrained females on sexual behavior of bulls. Twelve Angus bulls were used in three Latin square replicates where sexual interactions between one bull and one female were quantified for each of four 60-min tests (T1, T2, T3, and T4, respectively). All bulls received the following treatments: 1) exposure to four estrual females in sequence (A-B-C-D); 2) exposure to two estrual females in alternating sequence (E-F-E-F); 3) exposure repeatedly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…As the study progressed, perhaps the bulls became less interested or more accustomed to the presence of the cycling beef females. Perhaps the introduction of novel estrual females every month would have altered reproductive behavior outcomes to be more similar to those found in Bailey et al [17]. Generally, the sexual behavior assessed in the present study do not appear to change significantly with pubertal development and though exposed bulls had ample opportunity to interact with cycling females, display of sexual behaviors are not consistently altered by female presence beyond the periods of being a potential novel stimulus.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…As the study progressed, perhaps the bulls became less interested or more accustomed to the presence of the cycling beef females. Perhaps the introduction of novel estrual females every month would have altered reproductive behavior outcomes to be more similar to those found in Bailey et al [17]. Generally, the sexual behavior assessed in the present study do not appear to change significantly with pubertal development and though exposed bulls had ample opportunity to interact with cycling females, display of sexual behaviors are not consistently altered by female presence beyond the periods of being a potential novel stimulus.…”
Section: Discussionsupporting
confidence: 75%
“…Increased mounts and time spent in the cow area during month three may be a reflection of the change in females used though assessments were conducted almost a month after the new group of females was introduced, ample time for bulls to adjust to their presence before our observations. Bailey et al [17] reported that exposure of mature bulls to novel estrual females for 60 min at a time elicited a greater sexual behavioral response than exposure to either the same female in estrus or to a female in diestrus. After the introduction of the new females in our study during month three, reproductive behaviors either remained relatively constant or decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Bulls were sequestered in the testing pens, and equal numbers of females were distributed randomly within the pretest observation pens, still sequestered from the bulls. Video-recording equipment was set to capture all events in all pens simultaneously on one video cassette tape as previously described (Bailey et al, 2005). Females were allowed into pens either sequentially and switched every 30 min (SEQ) or as a group for 2 h (GRP; Figure 1C).…”
Section: Behavior Test Proceduresmentioning
confidence: 99%
“…A particular group of females served as sexual stimuli for all three groups of bulls on each test day. Each group of bulls was allowed to observe mounting activity among the females as described previously (Bailey et al, 2005); additionally, the last two groups of bulls were allowed to view heterosexual activity. By consistently monitoring female mounting activity, we were able to ensure that only females allowing mounting were placed with bulls during subsequent tests.…”
Section: Behavior Test Proceduresmentioning
confidence: 99%
See 1 more Smart Citation